Evaluation of Pharmacy Service Implementation in Class C Hospitals in Kebumen and Improvement Strategies - Muchromin Muchromin; Tri Wijayanti; Lucia Vita Inandha Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Health is a fundamental human right, and pharmacy services are a vital component of the healthcare system, especially in hospitals. The Ministry of Health Regulation No. 72 of 2016 serves as a guideline for implementing pharmacy services to ensure optimal healthcare delivery. Objective: This study aims to evaluate the implementation of Ministry of Health Regulation No. 72 of 2016 regarding pharmacy services in three class C hospitals in Kebumen Regency and to formulate improvement strategies using the Hanlon method. Method: A descriptive-analytical approach with a cross-sectional design was used. Data were collected through observations and interviews with the heads of pharmacy departments in the three hospitals. Results: The implementation of pharmaceutical supply management and clinical pharmacy services achieved 72.7% of the established standards. Key activities such as prescription review, medication history tracking, and counseling were conducted. However, activities like Drug Use Evaluation, sterile dispensing, and Therapeutic Drug Monitoring were not implemented due to limited facilities and skilled personnel. Hanlon analysis identified priority issues, including drug procurement accuracy, the number of items per prescription, and the lack of Drug Use Evaluation and Therapeutic Drug Monitoring. Conclusions: To improve service quality, recommendations include increasing budget allocation, training medical staff, and improving infrastructure. Addressing these issues is expected to enhance patient safety, drug use efficiency, and overall service satisfaction in the hospitals.